Utilization of Algerian calcined clay in sustainable mortars considering thermal treatment and granulometry effects on mechanical properties - Mouna Badaoui; Kamel Hebbache; Abdellah Douadi; Lamia Mansouri; Abdelghani Merdas; Soria Gherbi; Karima Kada; Mourad Boutlikht; Cherif Belebchouche; Jacek Szymanowski (Scientific Reports)
Abstract This study investigates the potential of calcined Algerian clay as a supplementary cementitious material (SCM) for enhancing the sustainability of cement production by reducing the consumption of clinker and emissions of carbon dioxide (CO₂). The research novelty lies in the comprehensive evaluation of fineness effects, the statistical modelling of mechanical performance, and the assessment of the environmental impact. A case study of practical significance is also provided. Clay was thermally activated at 700 °C to achieve near-complete dihydroxylation, ground to fineness levels of 45 µm and 80 µm, and then incorporated into the cement at replacement ratios of 10–30% by weight of the cement. Compressive and flexural strengths were assessed at 2, 7, and 28 days, while thermal and structural modifications were analysed using thermogravimetric analysis (TGA) and Fourier-transform infrared spectroscopy (FTIR). The results demonstrated that at lower substitution levels (10–15%), the 80 µm fraction of clay enhanced early-age compressive strength (13.6 MPa at 2 days), whereas at higher replacements (20–30%), the 45 µm fraction exhibited superior long-term strength (36.85 MPa at 28 days), which was attributed to improved pozzolanic reactivity and matrix densification. Flexural strength increased by 7–20% for substitution rates up to 20%, in turn confirming the structural benefits of calcined clay. Life-cycle analysis indicated significant reductions in energy consumption, CO₂ emissions, and production costs, with the M30–45 and M30–80 mixtures achieving reductions of approximately 10.6%. The statistical modeling of compressive strength at 2 and 28 days demonstrated high predictive accuracy, with coefficients of determination (R2) of 0.93 and 0.81, respectively. These models were statistically validated using analysis of variance (ANOVA), confirming their significance at a 95% confidence level (p < 0.05). These findings showed calcined Algerian clay to be a viable SCM, with it demonstrating enhanced mechanical performance, environmental sustainability, and economic feasibility, thereby contributing to the decarbonization of the cement industry.